Environmental Arsenic in a Changing World (Taylor & Francis, 2023)
The Congress ""Arsenic in the Environment"" offers an international, multi- and interdisciplinary discussion platform for research and innovation aimed towards a holistic solution to the problem posed by the environmental toxin arsenic, with significant societal impact. The Congress has focused on cutting edge and breakthrough research in physical, chemical, toxicological, medical, agricultural and other specific issues on arsenic across a broader environmental realm. The Biennial Congress ""Arsenic in the Environment"" was first organized in Mexico City (As2006) followed by As2008 in Valencia (Spain), As2010 in Tainan (Chinese Taiwan), As2012 in Cairns (Australia), As2014 in Buenos Aires (Argentina) and As2016 in Stockholm (Sweden). The 7th International Congress As2018 was held July 1-6, 2018, in Beijing, P. R. China and was entitled Environmental Arsenic in a Changing World.